Fabrication and conductivity enhancement of carbon nanotube transparent conducting film via solid state protonation - Ang, Derrick Eng Seng (2010)
At present, Indium-Tin-Oxide (ITO) is widely used as the transparent conducting electrodes in optoelectronics devices. The increasing of market demand causes the sustainability of this material to be questioned due to its scarcity, high cost and toxicity. Thus, to sustain the demand of such devices, an alternative replacement for conventional ITO has to be developed. In this aspect, Carbon Nanotube (CNT) has always been a promising candidate to replace ITO because of its excellent properties, availability and cost. However, the performance of CNT electrodes is still not comparable to those of ITO. A widely use approach is to employ acid treatment to further enhance the conductivity of the CNT thin films. In this project, different types of CNTs were air-sprayed and investigated to identify the potential CNTs as an alternative replacement for ITO. It was found that the quality of CNTs from different manufacturers differed greatly due to the difference in fabrication and purification technique of each manufacturer. To better understand the factors of conductivity of the CNT films, several important points for the fabrication of conductive CNT films were discussed: 1) diameter of CNT, 2) purity of CNT and 3) selective population of CNT. Dispersion quality of CNT was also performed by varying 2 parameters: 1) the presence of surfactants and 2) CNT concentration. At 0.5mg/ml with 0.5wt% of 4-dodecylbenzenesulfonic acid (SDBS), the best film conductivity was achieved; P3 CNTs obtained 70 ohm/sq at 62% transparency (T) and 45 ohm/sq at 48% T. Protonation, by using Bronsted acid such as HNO3, H2SO4, H2O2, was discussed in detail as the conductivity mechanism of the solid thin CNT films.